Impact of long working hours on health based on observations in China - Liming Chu (BMC, 2021)
Abstract Background Health should be a key focus in considerations of long working hours. Little is known about for which groups of people working longer hours is more harmful to their health. Additionally, the definition of long working hours varies slightly due to country differences in working hours systems. Therefore, this study aims to explore the association between long working hours and the self-rated health (SRH) level, taking into account gender and educational differences. Method Data were collected from two waves (2016 and 2018) of the China Family Panel Studies (CFPS). A total of 6972 workers were available for analysis. Descriptive statistical analysis, an ordered probit (oprobit) model and conditional mixed process (CMP) regression analyses were used to analyze the data. Furthermore, I conducted a stratified analysis by gender and education groups. Result This study observed a negative association between long working hours and SRH. Compared to other education groups, labor with long working hours had a more negative impact on the SRH of those with higher education. Long working hours had a more negative influence on the SRH of male workers. In contrast, no clear association was found among female workers. Conclusion This study estimates SRH of those with long working hours in China. Among workers, long working hours have a negative impact on the health of workers with college degrees or beyond. One possible explanation is that they do not exercise, their diet is unreasonable, and their working conditions involve chronic exposure to computer radiation. The negative health effects of long working hours on males are four times greater than those on females. This study provides valuable insights into the health of the workforce, working time regulations and overtime rules.